Descriptive Taxonomy : The Foundation of Biodiversity Research - Watson, Mark F.; Lyal, Chris H. C.; Pendry, Colin A. (Cambridge : Cambridge University Press, 2014)
In an age when biodiversity is being lost at an unprecedented rate, it is vital that floristic and faunistic information is up to date, reliable and easily accessible for the formulation of effective conservation strategies. Electronic data management and communication are transforming descriptive taxonomy radically, enhancing both the collection and dissemination of crucial data on biodiversity. This volume is written by scientists at the forefront of current developments of floras and faunas, along with specialists from applied user groups. The chapters review novel methods of research, development and dissemination, which aim to maximise the relevance and impact of data. Regional case studies are used to illustrate the outputs and impacts of taxonomic research. Integrated approaches are presented which have the capacity to accelerate the production of floras and faunas and to better serve the needs of a widening audience.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Conservation biology; Nature conservation; Sustainable biodiversity